Gambar Pitutur Punakawan sebagai Inspirasi Penciptaan Video Kanal Tunggal - Stephanus Andre Triadiputra; Setyo bagus Waskito (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2022)
The rapid development of technology makes the world has no real boundaries. Dissemination of information occurs very quickly and easily. Modern society at all ages, most of them have equipment that allows them to be directly connected to information, entertainment and knowledge that comes from anywhere. As a result, clash of local values with foreign or external values is unavoidable. Javanese proverbs that often appear through pictures of pitutur clowns (Semar, Gareng, Petruk, and Bagong) in glass paintings have noble values that are useful for character building, especially for Javanese people. Pitutur pictures usually contain suggestions and prohibitions in life. Video illustration of the existing pitutur images, made with the chroma key (green screen) technique as the creation method used for its embodiment. As a result, single channel videos which are illustrations of pitutur images can be used as a medium for spreading the noble values of Javanese culture in the current millennial era.